A review of Salmon's Folsomia types from New Zealand (Collembola). Issue 2 (3rd July 2017) - Potapov, M.; Janion-Scheepers, C.
ABSTRACT: Type specimens of six species of the genus Folsomia Willem, 1902 described by J. Salmon were examined. Folsomia pusilla Salmon, 1944 syn. nov. is synonymised with Mucrosomia caeca (Wahlgren, 1906). Synonymy of Folsomia lunata Salmon, 1943 with M. caeca is verified. Three species are transferred from the genus Folsomia to other genera, resulting in Mucrosomia novaezealandiae (Salmon, 1943) comb. nov., Cryptopygus miradentatus (Salmon, 1943) comb. nov. and Proisotoma sedecimoculata (Salmon, 1943) comb. nov. Folsomia parasitica Salmon, 1943 syn. nov. is synonymised with Folsomia candida Willem, 1902. Bagnallela is removed from the list of synonyms of the genus Folsomia. Proisotoma dubia (Deharveng, 1981) comb. nov. gets a new generic position.